PENYIDIKAN TINDAK PIDANA MONEY LOUNDERING DI KEJAKSAAN NEGERI JAKARTA PUSAT - Nico Yulianto Prabowo; Dewa Nyoman Sekar; I Ketut Sudjana (Kertha Negara : Journal Ilmu Hukum, 2013)
The convention or transfer of property, knowing that such property is derived from any serious (indictable) offence or offences, or from act of participation in such offence or offences, for the purpose of concealing or disguising the illicit of the property or of assisting any person who is involved in the commission of such an offence or offences to evade the legal consequences of his action; or The concealment or disguise of the true nature, source, location, disposition, movement, rights with respect to, or ownership of property, knowing that such property is derived from a serious (indictable) offence or offences or from an act of participation in such an offence or offences.